ANALISIS HUKUM ISLAM TERHADAP PEMENUHAN HAK NAFKAH ANAK PASCA PERCERAIAN AKIBAT PERSELINGKUHAN - Nisa, Maulida Zuchrotun; Ahsan, Khoirul (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2026)
The obligation to provide child support is a binding responsibility of the father that does not cease even if the marriage has ended due to divorce. The phenomenon of divorce resulting from infidelity, particularly among social media users, has the potential to affect the fulfillment of this obligation. This study aims to analyze patterns of child support fulfillment following divorce due to infidelity among social media users and to examine these practices from an Islamic legal perspective. This study employs an empirical legal method with a qualitative approach. Data collection was conducted online. Data analysis comprised three stages: data reduction, data display, and conclusion drawing and verification. The validity of the data was ensured through methodological triangulation and source triangulation. The results indicate three patterns of child support fulfillment identified among seven informants: (1) complete failure to provide support, which is the dominant pattern, influenced by the former husband forming a new family, poor communication, and low awareness of the father’s responsibility toward the child; (2) inconsistent fulfillment of child support due to the former husband’s shifting priorities toward his new family; and (3) routine and consistent fulfillment of child support. From an Islamic legal perspective, the first and second patterns contradict the obligation of child support as stipulated in Islamic law. The third pattern, however, aligns with the established provisions of Islamic law. This study emphasizes the importance of legal awareness and moral responsibility for fathers in fulfilling their children’s maintenance rights, even after the marriage has ended.